Contactless sociology: new forms of research in a digital age - O. Kryshtanovskaya (Цифровая социология)
Nowadays, digital sociology is becoming a reality. Online surveys, polls without the participation of the respondents based on the analysis of activities in social networks give the sociologist a unique opportunity to conduct a “contactless” research in which the respondent doesn’t know about the interest of the scientist to him. The networks already have all the answers, and the sociologist needs to find the right filters to extract the necessary information from the stream to subject it to intellectual analysis. The results of the political elite studies with the use of network and cluster analysis aimed at studying the activity and behavior of the Russian government official representatives in social networks have been described in the article. The analysis results identified four main clusters: “irreconcilable elite”, “negotiating elite”, “irreconcilable opposition”, “negotiating opposition” and the leaders of each cluster. The silence and closeness of the highest level of the Russian government as a certain political tradition are noted.